PENGARUH INTENSITAS MODAL, DIVIDEN PAYOUT RATIO DAN FINANCIAL DISTRESS TERHADAP KONSERVATISME AKUNTANSI (Studi Pada Perusahaan Sektor Energi Yang Terdaftar Di BEI) - Abdil alfaresi; Muhammad Fuad; Nasrul Kahfi Lubis (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
This study intends to discuss the Effect of Capital Intensity, Dividend Payout Ratio and Financial Distress on Accounting Conservatism (Study on Energy Sector Companies listed on the IDX). This research was conducted at energy sector companies listed on the Indonesia Stock Exchange (IDX) using secondary data obtained from the company's published financial statements. The data analysis method used is multiple linear regression and using statistical tools, namely SPSS (Statistical Product And Service Solutions) software. The results of this study indicate that Capital Intensity has a positive and significant effect on Accounting Conservatism, Dividend Payout Ratio has a negative and significant effect on Accounting Conservatism, Financial Distress has a positive but not significant effect on Accounting Conservatism and Capital Intensity, Dividend Payout Ratio and Financial Distress simultaneously have a significant effect. against Accounting Conservatism